ANALISIS ANGGARAN RESPONSIF GENDER PADA ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN TEMANGGUNG TAHUN ANGGARAN 2016 - Muhammad Alfatih Akbar Pahlevi; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2018)
Gender Responsive Planning and Budgeting (PPRG) is a planning made by all government agencies, professional organizations or other societies drawn up by considering four aspects: equal access, roles, benefits and controls between women and men. Planning and Budgeting needs to consider the aspirations, needs, and problems of women and men, both in the process of formulating and in the implementation of activities 212. Nevertheless, the implementation of PPRG in the regions has not been optimal, as well as the implementation and execution in the Regional Government of Temanggung Regency. With the less than optimal execution and implementation of PPRG, it is suspected that SKPD or the implementing agency of regional autonomy in the Temanggung Government is still not aware of whether it is a PPRG.This study aims to find out how the implementation of gender responsive planning and budgeting in the Regional Government of Temanggung Regency in 2016. Which, the authors will examine and interview some informants in some SKPD who have been able to implement PPRG. In the hope of obtaining comprehensive data related to PPRG. The research method used is an analytical descriptive in which this research seeks to find the widest knowledge of the object of research, to investigate in detail the activities or work of man, in this case is the work done in the Regional Government of Temanggung Regency in the management of PPRG.The results of this study indicate that the implementation and execution of PPRG implemented by SKPD or Agency in Local Government Temanggung Regency is still not optimal, because of the findings of research from 36 SKPD or Agency there are only 6 SKPD or Agency capable of implementing PPRG integrated with programs and activities implemented. Thus it can be concluded that the Regional Government of Temanggung Regency is still not optimal in the implementation of PPRG.Suggestions that can be submitted to the Local Government of Temanggung Regency is that the Regional Government of Temanggung Regency can arrange the local policy, be it Regent or Local Regulation which clearly regulate PUG and PPRG, so that all SKPD or Agency will as a whole prepare programs and activities that respond gender, which will be arranged in PPRG and ARG, so that the implementation of PPRG in the Local Government of Temanggung Regency can run optimally.Keywords : PPRG, PUG, ARG, Local Government